2011
DOI: 10.1111/j.1747-0803.2011.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Impact Prevalence of Arterial Ischemic Stroke in Pediatric Cardiac Patients over Three Decades

Abstract: Introduction.  Over the past three decades, significant advances in treatment have improved the mortality of children with cardiac disease. The effect of these advances on the prevalence of arterial ischemic stroke (AIS) is unknown. We describe AIS in children with cardiac disease in the modern era. Design.  The prospectively enrolled Intermountain Pediatric Stroke Database (including Utah, Wyoming, Idaho, and Nevada) was queried for all patients less than 18 years old with new‐onset AIS between January 1, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…Children with congenital and acquired heart disease are known to be at greater risk for stroke than the general population. Hoffman et al 11 reported an overall incidence of 132 of 100,000 per year, 16-fold higher than the reported incidence in the general pediatric population of between 2 and 8 of 100,000 per year. 12,13 In our population, not surprisingly, a diagnosis of congenital heart disease was a strong independent risk factor for stroke.…”
Section: Discussionmentioning
confidence: 65%
“…Children with congenital and acquired heart disease are known to be at greater risk for stroke than the general population. Hoffman et al 11 reported an overall incidence of 132 of 100,000 per year, 16-fold higher than the reported incidence in the general pediatric population of between 2 and 8 of 100,000 per year. 12,13 In our population, not surprisingly, a diagnosis of congenital heart disease was a strong independent risk factor for stroke.…”
Section: Discussionmentioning
confidence: 65%
“…29,33 Specific in utero and perioperative neuroprotective strategies to achieve these goals should be further investigated. 49,50 The strengths of this study include the high proportion of children assessed at 4. …”
Section: Figurementioning
confidence: 99%
“…Neonates and children with cardiac disease comprise one of the highest risk populations for pediatric arterial ischemic stroke (AIS), with a reported annual incidence rate ranging from 132 of 100,000 children to one of 100 children 1,2 compared with two to eight of 100,000 in the general pediatric population. 3,4 This risk persists beyond childhood.…”
Section: Introductionmentioning
confidence: 99%
“…5 The prevalence of cardiac disease among children with AIS did not change between 1978 and 2009 despite improvement in acute medical and surgical management and outcomes in children with cardiac disease during this time period. 1 Underlying heart disease contributes to AIS risk through right to left shunting of blood, increased systemic venous pressure, depressed heart function with aberrant flow dynamics, arrhythmias, infective endocarditis, or thrombophilias. 6 In addition, life-saving interventions such as cardiac surgery, cardiac catheterization, and mechanical circulatory support come with the cost of AIS as a potential complication.…”
Section: Introductionmentioning
confidence: 99%